Pediatric radiology casebase - James, Charles A.; Braswell, Leah E.; Glasier, Charles M.; Greenberg, S. Bruce; Seibert, Joanna J. (Thieme, 2016)
Pediatric Radiology Casebase, Second Edition, is a highly anticipated revision of a bestselling board exam review and clinical reference. Each detailed case presentation explains the decision making behind the diagnosis, helping pediatric radiologists and residents easily manage similar cases in their daily practice.